2017
DOI: 10.22159/ijpps.2017v9i5.16284
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity Evaluation of Ethanol Extract of Indonesian Velvet Beans

Abstract: Objective: This research was conducted to determine the acute toxicity of ethanol extract of velvet beans (Mucuna pruriens) from Indonesia. Extract of Indonesian Mucuna pruriens seeds showed antiparkinson activity due to the presence of L-DOPA inadequate levels. However, research on the toxicity level of Mucuna pruriens seeds from Indonesia is still limited. Acute toxicity data are needed to make Mucuna pruriens as standardized herbal medicine for Parkinson disease. Methods:The dried seed of Mucuna pruriens wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Based on the results obtained, the LD 50 of HAMP after single oral administration to female rats, observed over a period of 14 days, is >2000 mg/kg body weight. Sardjono et al also showed non-toxic effect of MP seed extracts, but it was carried out using ethanol extract, which supports our study [27].…”
Section: Resultssupporting
confidence: 90%
“…Based on the results obtained, the LD 50 of HAMP after single oral administration to female rats, observed over a period of 14 days, is >2000 mg/kg body weight. Sardjono et al also showed non-toxic effect of MP seed extracts, but it was carried out using ethanol extract, which supports our study [27].…”
Section: Resultssupporting
confidence: 90%
“…Previous studies showed the ability of SBT to increase blood HDL [14]. Other study results by Sardjono et al [20] showed the ability of velvet bean extract to increase blood HDL. Based on Table 4, VBT and VB-SBT have the potential as alternative foods to increase blood HDL like SBT.…”
Section: Analysis Of Serum Biochemical Profilementioning
confidence: 91%
“…Velvet beans have also been reported to have hypocholesterolemic properties. Several possible reaction mechanisms associated with velvet bean's hypocholesterolemic properties include inhibiting cholesterol biosynthesis in the body, preventing LDL oxidation due to its flavonoid content, converting cholesterol into bile acids, and inhibiting cholesterol absorption in the digestive tract [20].…”
Section: Analysis Of Serum Biochemical Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Subgroup-5 (sodium arsenite + M. pruriens) received sodium arsenite in drinking water (50 mg/L) + M. pruriens at a dose of 350 mg/kg BW [ 22 ] orally once per day for 45 days.…”
Section: Methodsmentioning
confidence: 99%